2010
DOI: 10.7143/jhep.37.484
|View full text |Cite
|
Sign up to set email alerts
|

Study on Causes and Ratio of the Liver Function Abnormalities in General Health Check-up

Abstract: Purpose Since most of chronic liver diseases progress with no symptoms, health checkup plays an important role as triggers for further examinations and treatments. Here, we studied the proportion of liver dysfunction among patients receiving health checkup , and investigated the causes. Method The study targeted 42,003 subjects who underwent health checkup at the PL Tokyo Health Care Center between April 2007 and March 2008. We selected subjects showing liver dysfunctions with readings of GPT40-79 IU/ml and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Increased HDL-C levels had negative associations with the development of liver damage, suggesting that an increase in HDL-C may protect the liver [ 45 ]. The negative association of older age with the development of liver damage is in agreement with both a cross-sectional study [ 37 ] and a longitudinal study [ 48 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Increased HDL-C levels had negative associations with the development of liver damage, suggesting that an increase in HDL-C may protect the liver [ 45 ]. The negative association of older age with the development of liver damage is in agreement with both a cross-sectional study [ 37 ] and a longitudinal study [ 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…A Japanese group also reported that among subjects receiving health check-ups, liver dysfunction defined as ALT ≥ 40 IU/L was found in 15.4% in men. The most common cause of elevated ALT was fatty liver, with this accounting for liver dysfunction in 13.0% of males [ 37 ]. The reason for the causal association between increased HsCRP levels and liver damage defined as AST ≥40 IU/L is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Against such backgrounds, we so far followed up and reported the cases of fatty liver encountered on the occasion of health check-ups 1,2) . Currently, many of the researchers and clinicians involved in the care and management of liver disease shifted their targets to "obesity and hepatic dysfunction" i.e.…”
Section: Introductionmentioning
confidence: 99%